Real-time exercise load control using heart rate response during exercise on a stationary bicycle - Chung, K.; Park, S.; Kim, S.; Park, G. (Procedia Engineering, 2011)
The purpose of this study was to develop an algorithm for exercise load control and estimation of energy expenditure during bicycle exercise. In this study, forty-eight healthy volunteers participated and were tested graded exercise test using ramp protocol and four interval training programs. To define the exercise intensity and workload, %HRmax was used for participants exercise prescription. Exercise load of the four interval training programs was manually adjusted to maintain participant's target heart rate during the interval training, and heart rate and energy expenditure condition were measured during the exercise. We developed an algorithm to feedback exercise load and energy expenditure for the four interval training programs recursively to consider cardio-physiological state in real-time. The averages of simulated and measured exercise load and energy expenditure were 0.89 and 0.85 respectively. From the result, this algorithm allows accurate modeling of the heart rate response to training intensity and energy expenditure in real-time basis. The real-time estimated algorithm that collects heart rate during bike exercise could be used to control the exercise load and estimate energy expenditure for optimal training of an individual.